Evaluation of the Biochemical and Antioxidant Behaviour of Four Species Chenopodium quinoa Willd, Zea mays L., Triticosecale wittmack and Hordeum vulgare L. Effected by Oxidative Stress Caused by Water Stress - Bouchareb Radia; Belguet Assia; Semmar R. Narimene; Guendouz Ali (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Our study was conducted at the faculty of Sciences of the nature and life from Mentouri Brothers University of Constantine, (36°21′54″ N: 6°36′52″ E), altitude above sea level by 574 m in March 2022. Cereals and pseudo-cereals, the world's most important crop, are an important source of sustenance for humans and animals. In addition, they are distinguished by their high tolerance to abiotic stressors. Hydrological deficit is a major factor limiting agricultural production; the impact varies according to the species, the stage of development of the plant and the severity of the stress. This research aims to evaluate the impact of water stress on H2O2 and Malondialdehyde MDA adaptation mechanisms, as well as the quantification of proteins, glycine betaine, phenols and flavonoids that can affect drought in three local species (Triticale, Barley and Maize) and one exotic plant (Quinoa). We also recorded an induced increase in triticale, barley, maize and quinoa stressed in Hydrogen Peroxide (H2O2), Malondialdehyde (MDA), proteins and glycine betaine with a concentration varied from 228.75 and 404.58 µmol.g-1 FM, 4.92 and 20.84 µmol.g-1 DM, 1.35 and 3.21 mg.g-1 FM, 0.34 and 0.54mg.g-1 DM, respectively. While the concentration of flavonoids and phenols total was recorded in maize by 20.14 mg QE g-1 DM and 375.47 mg GAE g-1 DM, respectively. Moreover, it reduced in triticale, barley and quinoa, with a value of 4.26-9.9 mg. EQ g-1 DM and 185.97-421.31 mg. EAGg-1 DM. The study demonstrated the species' resistance to and effectiveness in the face of water stress.